Causes of change in nitrophytic and oligotrophic lichen species in a Mediterranean climate: impact of land cover and atmospheric pollutants - Pinho, P. (2011)
ACESSO via B-on: http://dx.doi.org/ 10.1016/j.envpol.2007.11.028